An assessment of the recordkeeping practices of the Curial Offices of the Diocese of Malolos towards the development of a diocesan records management and archives policy framework - Avila, John Paul H. (2013)
This study sought to identify the strength and weaknesses of the recordkeeping practices of the Diocese of Malolos, particularly in the eleven curial offices, via the records life cycle, the records continuum concept, and the canonical and ecclesiastical provisions of the Catholic Church. Using the descriptive method of research, interviews with the curial office heads, group of discussions with the curial secretaries, as well as observation of curial office recordkeeping processes, were conducted. It was found out that although most of the curial offices employ best practices in creating, maintaining, using, and disposing their current records according to the nature of their tasks, there was no uniform practice that fulfilled the need to document, preserve, and promote records of enduring value. Some of the strengths noted in diocesan recordkeeping practices included the keeping of records as evidence of business transactions, the use of basic storage tools and maintenance equipment, and the installation of basic security equipment. The weaknesses determined by the study included issues in records receipt and transmission, outdated records inventory lists or total absence thereof, the lack of preventive maintenance for standard storage and security equipment, the absence of a records disposition schedule and the lace of integration of records control processes. The study also highlighted the importance of standardization of recordkeeping practices, accountability and training needs as key considerations for the formulation and implementation of a records management and archives policy. These key considerations became the framework upon which a proposed records management and archives program were based.